Unpacking the monolith: Intersecting gender and citizenship status in STEM graduate education. Issue 9 (25th September 2019) - Miner, Michael A.
Abstract : Purpose: The term STEM often remains an undifferentiated category, especially at the graduate level. Conceptualizing STEM as a monolithic category, rather than as a combination of distinct fields, prevents researchers from understanding and documenting the full range of persistent inequality within scientific disciplines at the graduate level and throughout the lifespan. The purpose of this paper is to address two oversights prior to degree completion within the context of the USA by asking two specific questions: To what extent is gender associated with choice of discipline within STEM graduate education? In the USA, do gender differences in STEM fields depend on citizenship status? Design/methodology/approach: Using data from the 2015 International STEM Graduate Student in the US Survey, this study employs multinomial logistic regression analyses and presents predicted probabilities to assess differences of enrollment in STEM fields by gender and citizenship status. Findings: Results show that domestic women were less likely to enroll in computer sciences and engineering when compared to domestic men. However, in contrast to domestic students, there were no gender differences among international students' enrollment in engineering. Research limitations/implications: This paper shows the importance and complexity of how gender intersects with citizenship status in enrollment patterns in STEM graduate fields. The survey included the top 10 universities in the USA based on the total enrollment of international students, and it is unclear if there exists differences in these selected students and schools when compared to students at colleges and universities that enroll less international graduate students. Originality/value: The author makes the case to disaggregate STEM to better assess how specific fields can be modified to attract graduate students worldwide. This paper accentuates the significance of gender and citizenship status for understanding differences in choice of discipline among graduate students in STEM.